2015
DOI: 10.3732/ajb.1400257
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of environmental variability on growth and survivorship of pre‐reproductive Joshua trees, Yucca brevifolia Engelm. (Agavaceae)

Abstract: A rare establishment event for Y. brevifolia during 1983-1984, triggered by above-average summer rainfall, provided a unique opportunity to track early survival and growth. Infrequent but acute episodes of herbivory during drought influenced demography for decades. Variability in survival among young Y. brevifolia indicates that size-dependent demographic variables will improve forecasts for this long-lived desert species under predicted regional climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…While recruitment for this species may be infrequent due to multiple factors (Reynolds et al 2012), this study as well as the study of Barrows and Murphy-Mariscal (2012) found many trees under 1 m (presumably younger than approximately 20-30 yr by the calculations of Esque et al 2015) in height across the park. The macroplots represented a wide range of densities, especially of juveniles, with one macroplot containing none at all, to more than 70 juveniles.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…While recruitment for this species may be infrequent due to multiple factors (Reynolds et al 2012), this study as well as the study of Barrows and Murphy-Mariscal (2012) found many trees under 1 m (presumably younger than approximately 20-30 yr by the calculations of Esque et al 2015) in height across the park. The macroplots represented a wide range of densities, especially of juveniles, with one macroplot containing none at all, to more than 70 juveniles.…”
Section: Discussionmentioning
confidence: 46%
“…As a proxy for age of Joshua trees (see Gilliland et al 2006 andEsque et al 2015 for discussion), teams measured height to the tallest part of the crown (along the axis of the trunk for trees that were leaning), living condition (a qualitative, categorical rating scale for overall plant condition from 2 (few shoots alive) to 5 (most shoots alive), and number of clonal sprouts on all living trees that we encountered within the macroplots. Macroplots were censused using a walking inventory navigating with the use of GPS units, covered generally in 25-m swaths by small teams of 3-5 individuals.…”
Section: Field Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations